SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN KERNEL SAWIT DENGAN METODE ANALYTICAL HIERARCHY PROCESS - Badariatul Lailiah; Rabiatus Sa’adah; Windu Gata; Verra Sofica (Elkom : Jurnal Elektronika dan Komputer, 2020)
Oil palm is Indonesia's leading and prime plantation commodity. Plants whose main products consist of palm oil (CPO) and palm kernel oil (KPO) have high economic value and are one of the largest foreign exchange earners compared to other plantation commodities (Fauzi, 2012) PT. Safety Pin River Purun is a company that manages palm kernel products with the products produced there are 2 types, namely CPKO (Cruide Palm Kernel Oil) and PKM (Palm Kernel Meal). From the results of the study it was found that the prototype design was made capable of producing palm kernel assessment calculations using AHP in the assessment process, while the prototype model used was to use the prototyping model method. With this research can be beneficial for the management of PT. The Sungai Purun pin in the process of evaluating palm kernel is more effective and accurate in producing reports